Characteristics of Surgical Necrotizing Enterocolitis: Is It Different from Medical Necrotizing Enterocolitis? A Single-Center Retrospective Study - Ara Cho; Dayoung Ko; JoongKee Youn; Hee-Beom Yang; Hyun-Young Kim (MDPI AG, 2021)
(1) Background: Necrotizing enterocolitis (NEC) is one of the leading causes of death in newborns despite improvements in the care of critically ill neonates. Approximately 50-70% of the cases are managed by medical therapy. However, the remaining patients require surgical intervention. The purpose of our study was to analyze the factors associated with patients requiring surgical treatment compared to patients requiring only medical treatment; (2) Method: Patients diagnosed with necrotizing enterocolitis over a period of 14 years (January 2003-December 2016) in a single tertiary referral children's hospital were retrospectively enrolled. Demographics and clinical data were collected through the medical record and were analyzed using Pearson's χ2 test, t-tests, and linear regression; (3) Results: A total of 189 NEC patients were analyzed. In the surgical NEC group, gestational age was lower (p = 0.018), body weight at birth was lower (p = 0.034), comorbidity with respiratory distress syndrome (RDS) was higher (p = 0.005), the days of antibiotic use were greater (p = 0.014), the percentage of breast milk feeding was lower (p = 0.001), and the length of hospital stay was longer (p < 0.000). The in-hospital mortality between the two groups was not significantly different (p = 0.196). In multivariate logistic analysis, breast milk feeding remained less associated with surgical NEC (OR = 0.366, 95% CI: 0.164-0.817), whereas the length of hospital stay was more associated with surgical NEC (OR = 1.010, 95% CI: 1.001-1.019); (4) Conclusion: Comparing medical and surgical NEC, a significantly lower percentage of surgical NEC patients were fed breast milk and their hospital stays were longer.